MR‐based field‐of‐view extension in MR/PET: B0 homogenization using gradient enhancement (HUGE). Issue 4 (30th November 2012) - Blumhagen, Jan O.; Ladebeck, Ralf; Fenchel, Matthias; Scheffler, Klaus
<x xml:space="preserve">Abstract</x> In whole‐body MR/PET, the human attenuation correction can be based on the MR data. However, an MR‐based field‐of‐view (FoV) is limited due to physical restrictions such as B0 inhomogeneities and gradient nonlinearities. Therefore, for large patients, the MR image and the attenuation map might be truncated and the attenuation correction might be biased. The aim of this work is to explore extending the MR FoV through B0 homogenization using gradient enhancement in which an optimal readout gradient field is determined to locally compensate B0 inhomogeneities and gradient nonlinearities. A spin‐echo‐based sequence was developed that computes an optimal gradient for certain regions of interest, for example, the patient's arms. A significant distortion reduction was achieved outside the normal MR‐based FoV. This FoV extension was achieved without any hardware modifications. In‐plane distortions in a transaxially extended FoV of up to 600 mm were analyzed in phantom studies. In vivo measurements of the patient's arms lying outside the normal specified FoV were compared with and without the use of B0 homogenization using gradient enhancement. In summary, we designed a sequence that provides data for reducing the image distortions due to B0 inhomogeneities and gradient nonlinearities and used the data to extend the MR FoV. Magn Reson Med, 70:1047–1057, 2013. © 2012 Wiley Periodicals, Inc.